Dakwah, Branding, dan Viralitas: Analisis Representasi Yakuza Maneges dalam Budaya Iklan Digital - Rohimah, Afifatur; Nurhalizah, Mevy Eka (Journal of Islamic Communication Studies, 2026)
This study aims to examine the extent to which social media has become a digital da'wah medium by leveraging a specific brand image or branding. The Yakuza Meneges Instagram account is the object of this research, as it utilizes digital subcultures, including branding, visual materials, emotional capital, and virality, which have truly revolutionized sermons. This study employed a qualitative approach using media text methods. Data were obtained through social media, graphic documents, written content, user comments, and an automated Instagram post management system. The results show that Yakuza Maneges utilizes social media to create religious iconography, visual power, and emotional influence to shape its brand image. The “Yakuza” movement, which evolved from a coercive attitude into a voluntary form of migration, is interpreted in today’s context as a narrative of spiritual transformation, masculine identity, and pilgrimage aesthetics. Social media algorithms and digital trends now play a major role in shaping modern online preaching, particularly in facilitating “santri jalur kiri”  young people who are interested in learning religion but have never had formal access to religious education. This condition reflects how digital da’wah activities on social media have gradually shifted spiritual practices toward industrialization, driven by visualization, identity construction, virality, and audience engagement.